Tile Partition Optimized Omnidirectional Video Coding for 6G Network - YANG Tao-yu, XU Yuan-yuan, TAN Zeng-jie (Jisuanji kexue, 2022)
The rise of the 6G wireless communication provides a broader prospect for the development of virtual reality panoramic video.The tile-based panoramic video coding scheme can improve the viewing experience of 360° video under the same condition of network bandwidth.Tile partition affects the video transmission performance.Compared with small tiles,using large tiles can effectively improve coding efficiency,but it will cause more pixel overhead by transmitting a larger area to cover the viewport.The existing tile partition work is mainly designed for the rectangular viewport,but the projection of spherical video to a two-dimensional plane will stretch different areas of the viewport to varying degrees in practice.Deriving the pixel overhead associated with covering irregular viewport areas with rectangular tiles is more complicated.To address this challenge,a tile partitioning algorithm for the user's real viewport has been proposed in this paper.Firstly,the stretching distortion of the viewport caused by the projection format is analyzed,and the pixel overhead of the irregular viewport with different tile partition sizes is derived.Secondly,by trading off the pixel overhead and the coding efficiency of tiles with different granularity,an optimal tile partition scheme has been proposed for the panoramic video sequence.Finally,the proposed scheme is compared with the exhaustive search method for tile partition in the experiment,and the results show that the proposed algorithm can achieve almost the same transmission efficiency as the exhaustive search method with less computational complexity.